-type functions with Hadamard gaps in the unit ball. Issue 6 (2nd June 2016) - Hu, Bingyang; Li, Songxiao
Abstract : We study the holomorphic functions with Hadamard gaps in -spaces on the unit ball of when and . A corollary on analytic functions with Hadamard gaps on -spaces on the unit disc is also given.